FAKTOR YANG MEMPENGARUHI KEPUTUSAN KONSUMEN PENGGUNA CASHLESS PAYMENT SYSTEM DALAM PEMBELIAN MINUMAN KOPI DI KOPI KALI PLACE - Gabriella, Maria; Perdana, Tomy (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Purchases of coffee beverages have increased partly due to the needs of people with high mobility and the new habits of WFH during the Covid-19 pandemic. In addition, the non-cash payment system in Indonesia has also increased quite rapidly through the Cashless Payment System. This requires coffee beverages businesses and Cashless Payment System companies to fulfill consumer wants and needs by following existing trends and technological developments. This study aims to describe the characteristics and decision processes of consumers when purchasing coffee beverages using the Cashless Payment System as a payment method, as well as to determine the factors that influence consumer decisions in purchasing coffee beverages through the Cashless Payment System at Kopi Kali Place. The research method used by researchers is descriptive analysis and factor analysis. Based on the results of the study, it shows that there are four new factors that influence the decision to purchase coffee beverages by users of the Cashless Payment System at Kopi Kali Place, namely, discount and promo factors, price and quality, ease of transaction, social and personal. The factors that contribute the most are discounts and promos, price and quality.